First report of Calpodes ethlius (Stoll, 1782) (Lepidoptera: hesperiidae) at altitude above 2000 masl - Gutiérrez-Bustamante, Silvia (2024)
The “achira” Canna edulis L. (Cannaceae) mainly distributed in South America and Mesoamerica, has been reported from a locality in North America, and introduced in Europe and Africa, as a host plant for larvae of Calpodes ethlius (Stoll, 1782) (Lepidoptera: Hesperiidae), which has a cosmopolitan distribution, with emphasis on the Neotropical region. Two adults of C. ethlius were recovered and deposited in the San Marcos Natural Museum, lima, Perú coming from larvae collected on “achira” leaves in a family orchard in the city of Caraz (9°02’40.9” S, 77°48’27.8” W) in Ancash, Peru. This is the first record of this hesperiid at an altitude higher than 2000 masl.